Strategi Manajemen Risiko Produk iB Kepimilkan Rumah Pada KB Bank Syariah KC Sidoarjo Prespektif Saddudz al-Dzari’ah - Hidayat, Bintang Kurnia; Ghozali, Muhammad Lathoif (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2025)
This research was conducted to analyze risk management strategies for the iB home ownership product at KB Bank Syariah KC Sidoarjo from the perspective of Saddudz al-Dzari’ah. This article adopts a qualitative research method, where primary data is obtained from interviews, to the extent that risk management is controlled by the bank. Meanwhile, secondary data was obtained in the form of journal archives and other references related to the research title. The research findings in this study indicate that KB Bank Syariah has an appropriate risk management strategy aligned with Saddudz al-Dzari’ah through its three lines of defense framework, which is in accordance with mafsadah and maslahah. It is hoped that future researchers can update the data and examine it more thoroughly.